The Economics of Financial and Medical Identity Theft - Camp, L. Jean.; Johnson, M. Eric.; SpringerLink (Online service) (Boston, MA : Springer US, 2012)
Financial identity theft is well understood with clear underlying motives. Medical identity theft is new and presents a growing problem. The solutions to both problems however, are less clear. The Economics of Financial and Medical Identity Theft discusses how the digital networked environment is critically different from the world of paper, eyeballs and pens. Many of the effective identity protections are embedded behind the eyeballs, where the presumably passive observer is actually a fairly keen student of human behavior. The emergence of medical identity theft and the implications of medical data privacy are described in the second section of this book. The Economics of Financial and Medical Identity Theft also presents an overview of the current technology for identity management. The book closes with a series of vignettes in the last chapter, looking at the risks we may see in the future and how these risks can be mitigated or avoided.
Identity in Economics, and in Context -- Modern Technological and Traditional Social Identities -- Identity Theft -- Defeating the Greatest Masquerade -- Secrecy, Privacy, Identity -- Security and Privacy as Market Failures -- Identity Theft in Healthcare -- Healthcare Data: Protections and Hemorrhages -- Technologies of Identity -- Identity Scenarios -- Scenario IV: Ubiquitous Identity Theft -- Closing -- References.
Keywords: Computer science; Medical records -- Data processing; Computer Communication Networks; Data protection; Data encryption (Computer science).; Biometrics; Computer Science; Systems and Data Security; Data Encryption; Health Informatics; Biometrics; Computer Communication Networks